2021
DOI: 10.3390/medicina57090968
|View full text |Cite
|
Sign up to set email alerts
|

Do Long-Term Complications of Type 2 Diabetes Increase Susceptibility to Geriatric Syndromes in Older Adults?

Abstract: Background and Objectives: Type 2 diabetes is one of the common chronic diseases in the elderly. It is thought that long-term complications of type 2 diabetes will negatively affect the quality of life in elderly individuals. It is possible that geriatric syndromes, especially frailty syndrome, are associated with diabetic complications, too. In this study, we aimed to evaluate the effect of macrovascular and microvascular complications of type 2 diabetes on frailty and other geriatric syndromes. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
0
14
2
Order By: Relevance
“…Indeed, previous studies have shown that DPN affects both quality of life and daily functions, not only in the older adults but also in the general population (28,29). A study conducted on older adults found that DPN affects ADLs but not IADLs (8). In our study, unlike this result, we found that DPN was not associated with ADLs but could be negatively associated with IADL.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Indeed, previous studies have shown that DPN affects both quality of life and daily functions, not only in the older adults but also in the general population (28,29). A study conducted on older adults found that DPN affects ADLs but not IADLs (8). In our study, unlike this result, we found that DPN was not associated with ADLs but could be negatively associated with IADL.…”
Section: Discussioncontrasting
confidence: 89%
“…We designed this study to draw attention to these inevitable results. In the current study, we observed that the rate of diabetic neuropathy was lower in married individuals; however, in some studies examining demographic data, no significant difference was found (8).…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…Blood glucose fluctuations are involved in the progression of chronic complications of diabetes through various processes. 21,22 It is thought that diabetic complications are more common in older individuals, and the macrovascular complications of diabetes were found to be associated with sarcopenia and decreased quality of life. Among microvascular complications, neuropathy is associated with possible sarcopenia and malnutrition.…”
Section: Discussionmentioning
confidence: 99%